(Czy) twórcza obecność osób niepełnosprawnych w przestrzeni publicznej? - Nieduziak, Edyta (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2015)
The aim of the article is the analysis of the works of disabled people in two levels: the first is the description of the artistic products; the second involves the use of creative activity in rehabilitation. The characteristics of the work has been referenced in WHO’s and IFC definitions of disability, M.I. Stein’s definition of creativity and the concept of levels of creativity by E. Nęcki combining them with such features as: autosubject resulting from being a person with a disability and the specific perception of the world as a consequences of disability. The creation process is used in a variety of forms of assistance for people with disabilities: social rehabilitation, occupational therapy, art therapy. However, each of them is conducive to the development of work at different levels. The highest level of creativity represent the modern Nikofors, whose works can be admired in the galleries.